2020
DOI: 10.1007/s11199-020-01148-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias in Student Evaluations of Teaching: Students’ Self-Affirmation Reduces the Bias by Lowering Evaluations of Male Professors

Abstract: This is the peer reviewed version of an article that has been accepted for publication in Sex Roles. An uncorrected and unedited version, it is not the version of reference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Furthermore, feedback immediately provided to the student causes the student to have a positive attitude towards continuous learning and be more involved in learning in terms of academic achievement. The final result of this study was that students who received immediate CF reached better AP (Cook & Artino Jr, 2016;Hoorens et al, 2021;Hunnikin et al, 2022;Mainhard et al, 2018). The results of studies have also shown that teachers' feedback has a positive effect on improving the level of emotions of students' academic achievement.…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, feedback immediately provided to the student causes the student to have a positive attitude towards continuous learning and be more involved in learning in terms of academic achievement. The final result of this study was that students who received immediate CF reached better AP (Cook & Artino Jr, 2016;Hoorens et al, 2021;Hunnikin et al, 2022;Mainhard et al, 2018). The results of studies have also shown that teachers' feedback has a positive effect on improving the level of emotions of students' academic achievement.…”
Section: Introductionmentioning
confidence: 71%
“…We also need to learn more about the conditions in which gender-based stereotypes are more and less likely to affect student ratings. For example, some research indicates that gender bias can be reduced by cautioning students against the use of stereotypes in the rating instructions (Hoorens, Dekkers, & Deschrijver, 2020;Peterson, Biederman, Andersen, Ditonto, & Roe, 2019).…”
Section: Women Psychological Science -33mentioning
confidence: 99%
“…We also need to learn more about the conditions in which gender-based stereotypes are more and less likely to affect student ratings. For example, some research indicates that gender bias can be reduced by cautioning students against the use of stereotypes in the rating instructions ( Hoorens, Dekkers, & Deschrijver, 2020 ; Peterson, Biederman, Andersen, Ditonto, & Roe, 2019 ). Other research has suggested that gender bias is stronger when students have received negative feedback ( Sinclair & Kunda, 2000 ), have lower grade expectations (e.g., Boring et al, 2016 ), or have been denied a request or favor (which are also more commonly asked of women professors; El-Alayli, Hansen-Brown, & Ceynar, 2018 ).…”
Section: Why Gender Gaps Exist In Psychological Sciencementioning
confidence: 99%
“…student evaluations, impact factors) is notoriously difficult and is easily biased by irrelevant criteria or incidental circumstances – such as teacher demographics (e.g. Hoorens, Dekkers, & De Schrijver, 2020). Further, to the extent that people are primarily assessed and rewarded for their personal achievements, this undermines their motivation to invest effort in the collaboration with others (Ellemers, De Gilder, & Haslam, 2004).…”
Section: Competitive Organizational Climatesmentioning
confidence: 99%